Influence of Organic Fertilizer Application on Durian (Durio zibethinus L.) Seedling Growth and Soil Nutrient Dynamics in Sumbawa Regency - Alfassabiq Khairi; Ayu Purnamasari (Jurnal Ilmu Pertanian, 2026)
Durian is an economically important tropical fruit in Southeast Asia; however, its productivity remains low in dryland areas such as Sumbawa Regency due to poor soil fertility and suboptimal cultivation practices. This study aimed to evaluate the effect of organic fertilizer application on the growth performance of durian seedlings and soil nutrient status. The experiment was arranged in a Randomized Complete Block Design (RCBD) with eight replications and eight treatments, consisting of organic fertilizer doses ranging from 0 to 100 g/plant. Growth variables were observed at early (12 days after planting, DAP) and vegetative stages (30–90 DAP), including hypocotyl and epicotyl characteristics, root development, plant height, number of leaves, and stem diameter. Soil chemical properties (pH, N, P, K, Ca, and Mg) were analyzed before planting and after harvest. The results showed that organic fertilizer significantly improved seedling growth and soil nutrient status. At 12 DAP, moderate fertilizer application (40 g/plant) produced optimal hypocotyl and epicotyl development, while the highest dose (100 g.plant-1) enhanced root biomass and total plant weight. During the vegetative stage, 100 g.plant-1 consistently resulted in the highest plant height, number of leaves, and stem diameter. Soil analysis indicated that organic fertilizer significantly increased the availability of essential nutrients (N, P, K, Ca, and Mg), although soil pH remained stable across treatments. Correlation analysis revealed strong positive relationships between plant growth variables and nutrient availability, particularly nitrogen and phosphorus. In conclusion, the application of organic fertilizer, especially at 100 g.plant-1, effectively improves durian seedling growth and soil fertility. This approach represents a sustainable strategy for enhancing durian cultivation in dryland environments such as Sumbawa Regency.